2017
DOI: 10.1080/02640414.2017.1398883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short- compared to long-haul international travel on the sleep and wellbeing of national wheelchair basketball athletes

Abstract: Currently, very little is known about the impact of short- or long-haul air travel on the sleep and wellbeing of wheelchair basketball athletes. Eleven national wheelchair basketball athletes wore actigraphy monitors prior, during, and after air travel to the United Kingdom. Upon arrival, participants rated their subjective jet-lag, fatigue, and vigor. Individuals traveled to the United Kingdom from different locations in Australia, the United States, and Europe and were categorised according to travel length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Sprint performance was also affected, especially in the first 72 h after landing [57]. Another study showed that not only long duration (up to 30h) but short (up to 6.5 h) duration east-west flights compromised sleep, increased fatigue and decreased vigor [58]. For the longer-haul flights, subjective fatigue and jet lag were significantly higher, wake-up time was earlier, and subjective vigor lower compared to the shorter flights (interestingly, these parameters were affected more than overall sleep) [58].…”
Section: Mitigating Jet Lagmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprint performance was also affected, especially in the first 72 h after landing [57]. Another study showed that not only long duration (up to 30h) but short (up to 6.5 h) duration east-west flights compromised sleep, increased fatigue and decreased vigor [58]. For the longer-haul flights, subjective fatigue and jet lag were significantly higher, wake-up time was earlier, and subjective vigor lower compared to the shorter flights (interestingly, these parameters were affected more than overall sleep) [58].…”
Section: Mitigating Jet Lagmentioning
confidence: 99%
“…Another study showed that not only long duration (up to 30h) but short (up to 6.5 h) duration east-west flights compromised sleep, increased fatigue and decreased vigor [58]. For the longer-haul flights, subjective fatigue and jet lag were significantly higher, wake-up time was earlier, and subjective vigor lower compared to the shorter flights (interestingly, these parameters were affected more than overall sleep) [58]. As a rough guide, jet lag symptoms may last for about one day per time zone crossed when traveling eastward, and a half-day per time zone crossed when traveling westward [59,60].…”
Section: Mitigating Jet Lagmentioning
confidence: 99%
“…Travelling long distances by plane presents a large effect on subjective grades of jet-lag, neurological fatigue and sleepiness. In particular, sleep and subjective responses are conceded, reflecting the travel requirements, matches atmosphere and environmental conditions ( Thornton et al, 2018 ) and (d) Adequate testing process of sport-specific performance with an appropriate use of monitoring technology ( Coutts, 2014 ), under implementation of technology in modern sports teams ( Torres-Ronda and Schelling, 2017 ). Moreover, main concrete specific mechanisms of fatigue with ad hoc training load analysis could inform about the most appropriate recovery methods ( Halson, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The NBA travel schedule induces misalignments in circadian rhythm that cannot be avoided. Air travel across three time zones has been reported to induce susceptibility to travel fatigue [ 18 , 29 , 42 , 43 , 44 ], increase injury risk [ 13 , 29 , 41 ], and reduce game performance [ 13 , 14 , 17 , 29 , 32 ]. NBA schedule-makers and teams may succeed in mitigating the negative effects of air travel from coast to coast on sleep by implementing up-to-date, evidence-based strategies applied in other professional sports, such as blue light exposure in the morning and red light exposure in the evening, in order to resynchronize the circadian rhythms of players [ 45 ].…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…First, it is important to understand the impact of air travel on NBA players at an individual level, given that NBA players often experience time zone transitions, which have been found to increase injury risk [ 9 , 41 ] and hinder performance [ 15 , 19 , 21 , 40 , 42 , 47 ]. Considering frequent time zone transitions often disrupt the circadian rhythm in athletes [ 15 , 16 , 19 , 26 , 42 , 43 ], future studies may focus on the measurement of salivary melatonin onset, adrenaline concentrations, and body temperature, as these are critical biomarkers of circadian rhythm [ 19 , 48 ]. Measurement of these biomarkers would provide insight into how each player individually adapts to air travel throughout the NBA season.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%